Population Growth Control Policy and Its Effect to Law Enforcement - Sinta Oktavina (Journal of Law and Legal Reform, 2020)
In minimizing population growth that occurs in Indonesia one of them can be done with a family planning program (KB) that has been carried out by the government. In accordance with the framework and ideals of the Indonesian people listed in the opening of the 1945 Constitution. The purpose of the study was to describe the implementation of improving population control through family planning programs in Semarang District in terms of Article 4 Paragraph (1) of the Central Java Regional Regulation No. 6 of 2013 and Knowing the supporting and inhibiting factors in overcoming population control through family planning programs in Semarang Regency. This legal research method uses a qualitative approach with a type of socio-legal research. The results of the study were obtained that (1) The implementation of family planning programs in Semarang Regency was carried out well from the central level to the field. The Office of PP, PA, and KB carry out regulations related to family planning programs which are the vision of the Regent. By communicating, providing information and education to the community and providing socialization and coordination in the implementation of family planning. (2) The supporting factor is the regulation on the implementation of family planning; there is reliable medical personnel. As for the inhibiting factors, not all communities accept the existence of a family planning program; community culture that is still strongly attached to each individual community. The conclusion is that the success of family programs goes very well and cannot be separated from community participation. So that it can be seen from the number of babies born can be reduced from 14,127 in 2015 and 13,328 in 2016 which are spread from 19 districts in Semarang Regency.